Urban perceptions: scenic performances and aesthetic experience in public space - Spinelli, Céline (Ilha Revista de Antropologia, 2022)
This article addresses scenic performances in public space and analyses how they are able to transform cities and their inhabitants. Although it derives from an ethnographic research carried out in the context of circus festivals, it is more a reflection anchored in an interdisciplinary matrix than an empirical contribution based on fieldwork. The purpose is to demonstrate how performances inscribes in the public space transforming both cities and the inhabitants’ perceptions about them. For this, we will observe the city as an ecosystem and some strategies used by artists to adapt their performances to the public space. Finally, we will focus on festivals that occupy cities allowing the realization of a complex set of performances. We will see that the aesthetic experience can trigger the spectators’ poetic imagination, being able to transform both the perceptions and the ties of belonging of the inhabitants to the city.